Konseling Konseptual: Sebuah Tinjauan Filosofis - Sri Astutik (Universitas Mathla'ul Anwar Banten, 2018)
CONCEPTUAL COUNSELING: A PHILOSOPHICAL REVIEW. Counseling is a process of giving help done by an expert (called counselor) to the individual who experienced a problem (called counselee) which leads to the overcoming problems facing him. Counseling serves as an effort to change, prevent or increase the potential of life. This literature study contains a description of the counselor's professional concepts in providing counseling services covering the meaning of counseling, counseling parameters, counseling and philosophy, counseling conditions and the effects of the professional counselor as well as the characteristics of a professional counselor which is seen based on the effectiveness of a helper.